Analisis Penerimaan Layanan Aplikasi Ijambikota Dengan Integrasi TFF Dan UTAUT - Yaticha, Ni Luh Ayu; Setiawan Assegaff; Benni Purnama (LPPM Universitas Dinamika Bangsa, 2025)
This study aims to analyze the acceptance of iJambiKota application services by integrating the Task Technology Fit (TTF) model and the Unified Theory of Acceptance and Use of Technology (UTAUT). The main focus of this research is to identify the extent of user acceptance of the iJambiKota application and what factors influence user decisions in adopting these applications. The TTF-UTAUT model combines eight variables, namely task characteristics, technology characteristics, task-technology fit, performance expectations, effort expectations, social influence, facilitating conditions, and user acceptance. As part of the methodology, questionnaires were distributed to 341 respondents, and the collected data were analyzed using the PLS-SEM method with the help of the SmartPLS tool. The analysis results show that the TTF-UTAUT model can explain 81.2% of the acceptance of iJambiKota application services. Factors that have a significant effect on acceptance include task and technology compatibility, performance expectations, effort expectations, social influence, and facilitating conditions. To encourage increased use of the iJambiKota application, it is recommended that there be more intensive socialization activities, innovation, and simulation of application features.